Answer:
The answer is B
Step-by-step explanation:
plz mark brainliest i answered first
Opposite angles in a parallelogram have to be equal so
3y=66
y=22
Answer: x = 50
Step-by-step explanation:
The simplified form of given expression is ![2x^3-5x^2-17x+20](https://tex.z-dn.net/?f=2x%5E3-5x%5E2-17x%2B20)
<em><u>Solution:</u></em>
Given that we have to simplify the expression
<em><u>Given expression is:</u></em>
![(x-4)(2x^2+3x-5)](https://tex.z-dn.net/?f=%28x-4%29%282x%5E2%2B3x-5%29)
We can simplify the expression by multiplying each term in first bracket with each term term in second bracket
![\rightarrow (x-4)(2x^2+3x-5)](https://tex.z-dn.net/?f=%5Crightarrow%20%28x-4%29%282x%5E2%2B3x-5%29)
![\rightarrow (x)(2x^2)+(x)(3x)+(x)(-5)-4(2x^2)-4(3x)-4(-5)](https://tex.z-dn.net/?f=%5Crightarrow%20%28x%29%282x%5E2%29%2B%28x%29%283x%29%2B%28x%29%28-5%29-4%282x%5E2%29-4%283x%29-4%28-5%29)
Simplify the above expression by multiplying the numbers in each term and adding the coefficients of like variables in each term
![\rightarrow 2x^3+3x^2-5x-8x^2-12x+20](https://tex.z-dn.net/?f=%5Crightarrow%202x%5E3%2B3x%5E2-5x-8x%5E2-12x%2B20)
Combine the like terms
![\rightarrow 2x^3+3x^2-8x^2-5x-12x+20](https://tex.z-dn.net/?f=%5Crightarrow%202x%5E3%2B3x%5E2-8x%5E2-5x-12x%2B20)
![\rightarrow 2x^3-5x^2-17x+20](https://tex.z-dn.net/?f=%5Crightarrow%202x%5E3-5x%5E2-17x%2B20)
Thus the expression is simplified
A = 143 m^2 because the height is 11 m and the width is 13 m if you add 9+4.